Applications of visually evoked potentials in ocular diseases: a guided tour - Vijean, Vikneswaran (IEEE Conference Publications, 2014)
Proceeding of The Student Conference on Research and Development (SCOReD 2011) at Cyberjaya, Malaysia on 19 December 2011 through 20 December 2011